Representations of sustainability and environmental welfare in Country Calendar. Issue 3 (2nd July 2020) - Craig, Geoffrey
ABSTRACT: This article examines representations of sustainability and environmental welfare in episodes of the iconic Aotearoa New Zealand television programme, Country Calendar . It initially locates the programme within the rural idyll myth and then outlines different understandings of sustainability while highlighting the normative basis of sustainability. The analysis identifies different portrayals of sustainability across episodes from the 2019 series, ranging from sustainable development, where sustainability practices are incorporated within existing economic and industry regimes, to more substantive expressions of sustainability that evoke different ways of living on the land and which more directly challenge dominant values of consumer capitalism. The analysis then reveals the 'content' of sustainability, ranging from enhancing soil quality to reduced plastic usage. Finally, the analysis also identifies the significance of social and cultural features of sustainability, ranging from community mobilisation to educational strategies that are put into practice on the farms.